ANALISIS PENGARUH VARIASI KUAT ARUS PENGELASAN METAL INERT GAS (MIG) TERHADAP KETANGGUHAN MATERIAL SAMBUNGAN LAS PADA BAJA ST 37 - Budi Priyono; Irzal Irzal; Hendri Nurdin; Primawati Primawati (Jurnal Vokasi Mekanika (VoMek), 2021)
This study aims to analyze the effect of variations in welding current strength on the toughness of MIG (Metal Inert Gas) welding with an ER 70S 6 (AWS A5.18) welding wire with a diameter of 1.2 mm on low carbon steel ST 37 with a thickness of 10 mm using rain.impact Charpy with ASTM E 23 standards. The method used in this study is an experimental method. This study aims to determine the effect of variations in the welding current strength against impact results MIG welding of steel ST 37 with a strong variation of the welding current 120 A, 140 A and 160 A. The result oftest Charpy Impact this isspecimen without welding control ortest results impact Charpy has anvalue Impact averageof 2.04 Joules / mm2, specimens with a welding current of 120 Ampere have anvalue Impact averageof 2.15 Joules / mm2 specimens with a strong welding current of 140 Ampere have anvalue value Impact an average of 2.20 Joules / mm2, the impact specimen with a welding current of 160 Ampere has anvalue Impact averageof 1.99 Joules / mm2, Based on thetest, the Charpy Impact results of MIG (weldingMetal Inert Gas) with variations in welding current strength of 120 A, 140 A, and 160 A can be concluded that from the results obtained there is a difference in the toughness of the material in absorbing energy from the shock load that hits it as well as the impact value on each specimen against the variation of the current given. This difference occurs because the effect of heat that occurs on the material increases according to the current strength received by the MIG welding material so that this affects the structure of the material being welded so as to make the toughness and impact value of each specimen obtained show different results.